Dynamic profiles of tar products during Naomaohu coal pyrolysis revealed by large-scale reactive molecular dynamic simulation. (1st October 2019) - Zheng, Mo; Li, Xiaoxia; Wang, Meijun; Guo, Li
Graphical abstract: Highlights: The largest model of 98, 748 atoms for Naomaohu coal ever simulated by ReaxFF MD. Detailed dynamic profiles of tar intermediates/structures in coal pyrolysis revealed. Strong relationship between tar composition and coal pyrolysis stages observed. Five- and seven-membered ring structures in tar should be the soot precursors. –O–(CH2 )n – linkages play a key role in low-temperature cross-linking reactions. Abstract: Understanding dynamic profiles of tar in coal pyrolysis is vital to high quality chemical production and upgrading process of tar, which is difficult to be accessed experimentally. Using large coal models with reasonable distribution of functional groups, ReaxFF MD method can shed light on comprehensive structures and reaction details of coal tar in pyrolysis, which complements available experimental observations. In this work, a large model with 98, 748 atoms of Naomaohu low-rank coal is constructed to explore tar behaviors for the first time computationally by heat-up ReaxFF MD simulations at 500–2500 K. The correspondence between the tar behaviors and the divided four pyrolysis stages observed would be very helpful for modulating the composition and yield of tar and the subsequent upgrading process. The dynamic profiles of bridge bonds, ring intermediates and the detailed structures of hydrocarbons in tar (C5 –C40 fragments) are revealed, which shows that the five- and seven-membered ring intermediates in tar should be soot precursors during coal pyrolysis process. The increasing trend of –O–(CH2 )n – is strongly related to low-temperature cross-linking reactions during low-rank coal pyrolysis, while the increasing trend of Car –Car plays a significant role in recombination reactions at high temperature. Moreover, the simulation also shows that the production of aliphatic hydrocarbons is favored at the primary pyrolysis stage, accompanied with high concentration of oxygenated compounds produced, while aromatic fragments are most likely generated at the secondary pyrolysis stage where the amount of phenolic products tends to decrease.